Association between serum fructose level and insulin resistance in women with polycystic ovary syndrome: The effect of obesity - hatem, ameera; O Saleh, Basil; M Al-Naddawi, Afraa (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Polycystic ovary syndrome (PCOS) women’s most prevalent endocrinology condition is a mixture of environmentally and genetically adduced causing PCOS. The relationship between monosaccharide and PCOS is largely unknown. Objective: This research was designed to investigate the relationship between blood levels of fructose, insulin resistance, and androgen hormone in women with PCOS, and the effect of obesity on the obtained result, as well as to study the efficacy of serum fructose as a biomarker in the diagnosis of PCOS. Cases and methods: This case-control research study was conducted at the Gynecology Clinic and Infertility Center, in Baghdad Teaching Hospital / Medical City between November 2021 to March 2022. It involved 120 women between the ages of 18-40 year. Fifty-nine women (cases) were newly diagnosed with PCOS by a gynecologist and 61 age and BMI matched healthy women (controls). PCOS women were subdivided according to their body mass index into four groups: lean, normal weight, overweight and obese. Investigations included serum measurements of fructose, luteinizing hormone (LH), follicular stimulating hormone (FSH), free testosterone, insulin, glucose, and calculated homeostasis model assessment- insulin resistance (HOMA-IR) and quantitative insulin sensitivity check index (QUICKI). Results: The mean ±SD values of serum fructose, glucose, insulin and HOMA-IR were significantly augmented in PCOS women as compared to controls (p< 0.001), while mean value of QUICKI was significantly decreased (p<0.0001). There was a significant positive correlation between BMI values and fructose levels in PCOS women. The result showed that serum fructose and free testosterone levels had the highest sensitivity and specificity in the differentiation between the PCOS group and the controls, with the area under curve values for free testosterone higher than area under curve values for fructose. Conclusions: The fructose level can be used as an alternative biomarker for women with PCOS independent of insulin resistance. The majority of PCOS women are obese and overweight, and a minority are lean who are severely complicated by insulin resistance.